Enterprise level security 2 advanced topics in an uncertain world - Foltz, Kevin E.; Simpson, William Randolph, 1946- (Boca Raton : CRC Press, 2020)
Enterprise Level Security 2: Advanced Topics in an Uncertain World follows on from the authors first book on Enterprise Level Security (ELS), which covered the basic concepts of ELS and the discoveries made during the first eight years of its development. This book follows on from this to give a discussion of advanced topics and solutions, derived from 16 years of research, pilots, and operational trials in putting an enterprise system together. The chapters cover specific advanced topics derived from painful mistakes and numerous revisions of processes. This book covers many of the topics omitted from the first book including multi-factor authentication, cloud key management, enterprise change management, entity veracity, homomorphic computing, device management, mobile ad hoc, big data, mediation, and several other topics. The ELS model of enterprise security is endorsed by the Secretary of the Air Force for Air Force computing systems and is a candidate for DoD systems under the Joint Information Environment Program. The book is intended for enterprise IT architecture developers, application developers, and IT security professionals. This is a unique approach to end-to-end security and fills a niche in the market.
Chapter 1. The First 16 Years. 1.1 The Beginning of Enterprise Level Security (ELS). 1.2 Design Principles. 1.3 Key Concepts. 1.4 Implementation. Chapter 2. A Brief Review of the Initial Book. 2.1 Security Principles. 2.2 ELS Framework. Chapter 3. Minimal Requirements for the Advanced Topics. 3.1 Needed Capabilities. 3.2 Creating an Attribute Store. 3.3 Registering a Service. 3.4 Computing Claims. 3.5 User Convenience Services. 3.6 The Enterprise Attribute Ecosystem. 3.7 Summary. Identity and Access Advanced Topics. Chapter 4. Identity Claims in High Assurance. 4.1 Who Are You?. 4.2 Entity Vetting. 4.3 Naming. 4.4 Key and Credential Generation. 4.5 Key and Credential Access Control. 4.6 Key and Credential Management. 4.7 Key and Credential Uses. 4.8 Some Other Considerations. Chapter 5. Cloud Key Management. 5.1 Clouds. 5.2 ELS in a Private Cloud. 5.3 The Public Cloud Challenge. 5.4 Potential Hybrid Cloud Solutions. 5.5 Proposed Secure Solutions. 5.6 Implementation. 5.7 Cloud Key Management Summary. Chapter 6. Enhanced Assurance Needs. 6.1 Enhanced Identity Issues. 6.2 Scale of Identity Assurance. 6.3 Implementing the Identity Assurance Requirement. 6.4 Additional Requirements. 6.5 Enhanced Assurance Summary. Chapter 7. Temporary Certificates. 7.1 Users That Do Not Have a PIV.. 7.2 Non-PIV STS/CA-Issued Certificate. 7.3 Required Additional Elements. 7.4 Precluding the Use of Temporary Certificates. 7.5 Temporary Certificate Summary. Chapter 8. Derived Certificates on Mobile Devices. 8.1 Derived Credentials. 8.2 Authentication with the Derived Credential. 8.3 Encryption with the Derived Credential. 8.4 Security Considerations. 8.5 Certificate Management. Chapter 9. Veracity and Counter Claims. 9.1 The Insider Threat. 9.2 Integrity, Reputation, and Veracity. 9.3 Measuring Veracity. 9.4 Creating a Model & Counter-Claims. 9.5 Veracity and Counter-Claims Summary. Chapter 10. Delegation of Access and Privilege. 10.1 Access and Privilege. 10.2 Delegation Principles. 10.3 ELS Delegation. 10.4 Delegation Summary. Chapter 11. Escalation of Privilege. 11.1 Context for Escalation. 11.2 Access and Privilege Escalation. 11.3 Planning for Escalation. 11.4 Invoking Escalation. 11.5 Escalation Implementation within ELS. 11.6 Accountability. 11.7 Escalation Summary. Chapter 12. Federation. 12.1 Federation Technical Considerations. 12.2 Federation Trust Considerations. 12.3 Federation Conclusions. ELS Extensions - Content Management. Chapter 13. &n
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measures; Industries -- Security measures; COMPUTERS / Cryptography; COMPUTERS / Groupware